Positive experiencing of loneliness as a factor of personality - Iryna Mukhanova; Vira Romanova (Social Welfare: Interdisciplinary Approach, 2013)
The article focuses on the theoretical analysis of such a phenomenon as loneliness and the forms of experiencing it. The article provides an empirical research of loneliness, isolation, separation and personality’s emotional intellect as determinants of possible positive experience of loneliness. No association is established between evaluation of notions of the semantic feld of loneliness and the degree of emotional intellect maturity.